13 μm fiber grating in a thin-core fiber for LP01–LP11 mode converters and sensing ability - Tong, Rongxin; Yang, Hangzhou; Lu, Kai; Lee, Yen Sian; Lim, Kok Sing; Ahmad, Harith; Hu, Manli (Optical Society of America, 2019)
We demonstrate an all-fiber structure that can realize LP01 − LP11 mode conversion and twist measurement. It is a thin-core fiber (TCF) grating at a wavelength of 1310 nm cascaded to a short segment of a TCF of a different core size. It is found that the different core size of the TCF between the fiber and the grating has an impact on the excitation of a higher-order mode and mode conversion efficiency. The fiber structure exhibits a good linear response to twisting, strain, and temperature. Depending on the associated mode, the mode intensity and the wavelength for exciting the peaks of the grating have different sensitivities to twisting angle, applied strain, and temperature. These properties can be exploited for simultaneous measurement. © 2019 Optical Society of America